Fuzzy Delphi method for A-level mathematics technological pedagogical and content knowledge module - Chinghao Chua; Azlina Mohd Kosnin; Kee Jiar Yeo (International Journal of Evaluation and Research in Education (IJERE), 2024)
This study sought to identify the elements for designing and developing the A-level mathematics technological, pedagogical, and content knowledge (TPACK) teaching module. The aim of the module was to incorporate various pedagogies and technological tools for helping mathematics teachers to trigger, maintain, as well as sustain students’ interest in learning mathematics. This study used the Fuzzy Delphi method to determine the consensus on how A-level mathematics instruction should be designed. A semi-structured interview had first been conducted to develop a questionnaire. Then, a group of 16 experts was consulted together to discuss their ratings and reach a consensus. The group of experts included educational technology and subject matter experts. Data analysis results showed that the experts accepted all these elements through the expert consensus value above 75%, the threshold value (d)≤0.2, and the Fuzzy score (A)≥α-cut value of 0.5. This research provides implication to A-level mathematics teachers to systematically create an environment that is more conducive to learning and that will ultimately lead to an increase level of students’ interest towards learning.